2020
DOI: 10.1371/journal.pmed.1003145
|View full text |Cite
|
Sign up to set email alerts
|

Health and cost impact of stepping down asthma medication for UK patients, 2001–2017: A population-based observational study

Abstract: Background Guidelines recommend stepping down asthma treatment to the minimum effective dose to achieve symptom control, prevent adverse side effects, and reduce costs. Limited data exist on asthma prescription patterns in a real-world setting. We aimed to evaluate the appropriateness of doses prescribed to a UK general asthma population and assess whether stepping down medication increased exacerbations or reliever use, as well as its impact on costs. Methods and findings We used nationwide UK primary care me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…In the UK, around two-thirds of asthma patients, that are managed with a preventer, use medium or high dose ICS. 1 It is unclear whose role it is to step down, arguably it is everyone's role, but many doctors and some nurses did not feel it was their responsibility. This may be a major contributing factor, for example doctors often suggested it should be assessed during a nurse-led asthma review, whereas some nurses reported feeling hesitant to step-down medication prescribed by a doctor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the UK, around two-thirds of asthma patients, that are managed with a preventer, use medium or high dose ICS. 1 It is unclear whose role it is to step down, arguably it is everyone's role, but many doctors and some nurses did not feel it was their responsibility. This may be a major contributing factor, for example doctors often suggested it should be assessed during a nurse-led asthma review, whereas some nurses reported feeling hesitant to step-down medication prescribed by a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…21 We feel our data was adequate in this respect and complementary to recent UK observational data. 1 However, it is possible there was some selection bias, such that those with an interest in asthma were more likely to participate. If this bias occurs, you may expect the health professionals that did not wish to participate were more likely to perceive the barriers we found.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations